Annals Graphic Medicine - Dear Doctor II - Councilor, KC (Annals of Internal Medicine, 2017)
Keywords: dept.com

Annals Graphic Medicine - Dear Doctor I - Councilor, KC (Annals of Internal Medicine, 2017)
Keywords: dept.com

Is it safe to bring myself to work? Understanding LGBTQ experiences of workplace dignity - Baker, Sara J; Lucas, Kristen (Canadian Journal of Administrative Sciences-revue Canadienne Des Sciences De L Administration, 2017)
Despite increased efforts by more organizations to be seen as “gay-friendly,” workplaces remain challenging sites for LGBTQ employees to navigate. We examine the ways in which LGBTQ employees experience dignity threats in the workplace and the protection strategies they use to deflect those threats. Interviews with 36 LGBTQ working adults revealed that their dignity is threatened by a range of identity-sensitive inequalities that undermine their safety and security when they claim authentic gendered/sexual identities. Specific safety and security threats to dignity include social harm, autonomy violations, career harm, and physical harm. To (re)claim their dignity, they engage in four primary dignity protection strategies: avoiding harm by seeking safe spaces, deflecting harm with sexual identity management, offsetting identity devaluations by emphasizing instrumental value, and creating safe spaces for authenticity and dignity. Copyright (C) 2017 ASAC. Published by John Wiley & Sons, Ltd.
Keywords: authenticity; dept.com; gay-friendly; heteronormativity; safety; sexual identity management; workplace dignity

Feeding the body politic: metaphors of digestion in Progressive Era US immigration discourse - Councilor, KC (Communication and Critical/Cultural Studies, 2017)
In the era between the 1882 Chinese Exclusion Act and the Immigration Act of 1924, nativist advocates for immigration restriction commonly invoked metaphors of eating and digestion to support their cases. This essay draws on political, popular, and scientific discourses around immigration and digestion in order to analyze the affective power of the rhetorically constructed “body politic.” While numerous scholars have addressed the ways immigrants have been variously figured as threats to the nation—as pollutants, toxins, disease, floods, or invading armies—few have analyzed metaphors of eating and digestion. I argue that the national body became a metonym for the ideal (white) citizen body, which supported anti-immigrant rhetoric through metaphors of eating, digesting, and eliminating undesirable aliens—those who did not agree with the national stomach. The body politic came to represent the ideal US American body as individuals were invited to identify with the nation through the trope of the body politic; immigrants who did not share this ideal body were rendered undesirable through their association with indigestibility and disgust. This essay demonstrates the affective and thus political power that digestion metaphors provided, shedding light on an early instantiation of the disgust that pulses through twenty-first-century anti-immigrant discourse in the United States.
Keywords: dept.com; digestion; immigration; nativism; race; rhetoric